ANALISIS JAWABAN TUGAS MAHASISWA PADA TUTORIAL ONLINE BERDASARKAN BLOOMS TAXONOMY - Sandra Sukmaning Adji (LPPM Universitas Terbuka, 2014)
The Open University (UT) provided by the educational staff of the Open University (UT) to help students overcome their learning difficulties. This paper focuses on the ability of students in doing the tasks, assigned by the tutor during the online tutorial activities. The study was conducted at the UT course tutorial activities of Environmental Chemistry Subject at the trial period of 2010.2, 2011.1 2011.2, 2012.1 and 2012.2 involving 81students. Data was obtained based on students answers to the assignments/tasks given by the tutor. The indicators used for analysis of students task answer were the students ability in Blooms taxonomy analyzing. The data then was analyzed into qualitative descriptive. Results showed: 1) All students were able to answer well for the ability of memory understanding and comprehension 2). Not all students were capable to reach higher level thinking i.e. analyzing and evaluating in answering the questions given. 3) Students gave positive respon in online tutorial activities and using the